2013
DOI: 10.1371/journal.pntd.0002315
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium ulcerans Disease: Experience with Primary Oral Medical Therapy in an Australian Cohort

Abstract: Background Mycobacterium ulcerans (MU) is responsible for disfiguring skin lesions and is endemic on the Bellarine peninsula of southeastern Australia. Antibiotics have been shown to be highly effective in sterilizing lesions and preventing disease recurrences when used alone or in combination with surgery. Our practice has evolved to using primarily oral medical therapy.MethodsFrom a prospective cohort of MU patients managed at Barwon Health, we describe those treated with primary medical therapy defined as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…This rate of adverse effects is in keeping with rates previously described for rifampin, clarithromycin, and ciprofloxacin in our experience (1,5,15), which are higher than rates reported for younger populations in Africa (7). The older median age of our cohort likely contributes significantly to reduced drug tolerability in our cohort (15).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This rate of adverse effects is in keeping with rates previously described for rifampin, clarithromycin, and ciprofloxacin in our experience (1,5,15), which are higher than rates reported for younger populations in Africa (7). The older median age of our cohort likely contributes significantly to reduced drug tolerability in our cohort (15).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in 2010, a randomized controlled trial in Ghana was published that found RS8 to have an efficacy similar to that of 4 weeks of rifampin-streptomycin followed by 4 weeks of rifampin-clarithromycin (RC) (RS4RC4) (8). These successes paved the way for the use of the fully oral combinations of rifampin and fluoroquinolones (RFQ) and RC in both Australia and Benin (1,5,9). Most recently, treatment success was demonstrated in Ghana with an even shorter duration of injectable streptomycin therapy of 2 weeks (RS2) followed by oral RC for 6 weeks (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations